Britain and international law in West Africa : the practice of empire - Hulle, Inge van (Oxford : Oxford University Press, 2020)
This text provides an in-depth contextual analysis of the role of international law in the growth of British presence in West Africa during the early- and mid-nineteenth century. It highlights this period as an important experimentation phase which saw the genesis of the treaties that have now become associated with the Scramble for Africa.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 16, 2020).
Keywords: Law -- Africa, West -- History -- 19th century; Great Britain -- Relations -- Africa, West; Africa, West -- Relations -- Great Britain